Comment on: Diagnostic reference levels for diagnostic and interventional X-Ray procedures in Germany: update and handling / Alexander Schegerer, Reinhard Loose, Lothar J. Heuser, Gunnar Brix) - Biederer, Jürgen; Hamer, Okka; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Kühl, Hilmar; Ley, Sebastian; Ley-Zaporozhan, Julia; Müller-Lisse, Ullrich G.; Vogel-Claussen, Jens; Wormanns, Dag (RöFo. Supplement, 2020)
Thieme E-Books & E-Journals